NOTARY'S ROLE AND AUTHORITY IN THE BUSINESS ENTITY TRANSFER OF THE FIRM INTO LIMITED COMPANY - Gunawan, Maria Febriana Widya; Putra, Mohamad Fajri Mekka (Awang Long Law Review, 2022)
This study investigates a notary's function in transferring a Business Entity. This study, which is analytical and descriptive, was conducted using a qualitative research design and is disseminated as a descriptive scientific paper. The statutory and conceptual approaches are used in this research's approach to the issue. Changing a Firm's legal structure to become a Limited Company heavily relies on a notary. The creation of authentic deeds for a variety of deeds, agreements, and stipulations, including the deed establishing a company, is permitted by a notary. Notaries have an essential role in researching the completeness of the files and the number of assets owned by the Firm that will be converted into a Limited Company. As is common knowledge, a Firm Partnership is a business alliance formed by two or more individuals using the same name.